Políticas habitacionais na federação brasileira: os estados em busca de seu lugar - Gonçalves, Renata da Rocha (2009)
This research presents an analysis of the place of state governments in Brazilian federation, more precisely, in their role in the production of public policies. In order to develop this argument, we analyse the trajectory of social housing policies in Brazilian states. Despite the fact that transformations in the national level have a significant impact across states, the particular responses of each state government to these impacts, their institutional pathways, and their modes of action are highly heterogeneous. The hypothesis that guides this research aims at demonstrating that: (1) the trajectory of certain public policies can differentiate the functions and performance of different government levels; (2) the institutional development of each state makes a difference and produces effects in its performance in the public policies. In a nutshell, the research shows how state governments have been searching for their place in Brazilian federation, considering the implementation of a specific public policy and how this role is varied and heterogeneous in the horizontal plan.